2009
DOI: 10.1007/s11469-009-9234-0
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of the Connection between Child Sexual Abuse and Gambling in Aboriginal Communities

Abstract: Child sexual abuse (CSA) lead to short-term sequelae and long-lasting pervasive outcomes. Research has started addressing CSA as a potential risk factor for later addictions, including pathological gambling. Among Aboriginal peoples, it is plausible that the legacy of residential schooling and other historical traumas have led to unresolved grief that contribute to social problems, such as pathological gambling. The purpose of this brief paper is to report on the few available studies examining the connection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 61 publications
(75 reference statements)
0
15
0
Order By: Relevance
“…According to a small, but growing body of evidence, these consequences may include gambling problems (see Dion, Collin-Vézina, De La Sablonière, Philippe-Labbé, & Giffard, 2010 for a literature review). However, few studies have been conducted on the impact of CSA on gambling among Indigenous Peoples.…”
Section: Introductionmentioning
confidence: 99%
“…According to a small, but growing body of evidence, these consequences may include gambling problems (see Dion, Collin-Vézina, De La Sablonière, Philippe-Labbé, & Giffard, 2010 for a literature review). However, few studies have been conducted on the impact of CSA on gambling among Indigenous Peoples.…”
Section: Introductionmentioning
confidence: 99%
“…Abusive environments appear to be associated with the development of depression, anxiety, or suicidal thoughts and attempts (Jacobs and Gill 2002;Young 2009, 2010), which have been shown to be linked to problem gambling. A recent study by Dion et al (2010) suggested that a history of child sexual abuse might contribute to the development of later pathological gambling among Aboriginal peoples and a study by Felsher et al (2010) reported similar findings among young non-native Canadians.…”
Section: Discussionmentioning
confidence: 78%
“…Gambling is a traditional activity of Aboriginal societies throughout the Americas (Gabriel 1999;Hill and Clark 2001) with documented use in ceremonial, recreational, political, and diplomatic events as early as 1000 years before Europeans arrived in North America (Belanger 2011;Dion et al 2010). In small isolated communities in the Cree territory, gambling has traditionally brought people together in a social activity that redistributed wealth within a closed system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two articles in this edition provide an illustration of how researchers are surveying the limited literature on problem gambling in Indigenous communities to try to identify the factors that are particularly deserving of further research. Dion et al (2010) provide an example of the difficulties of reviewing the literature linking childhood trauma and problem gambling, predominated by non-Indigenous studies, to explore possible links between sexual abuse and problem gambling amongst Aboriginal peoples in Canada. The second article compares gambling to smoking and alcohol, in terms of the negative consequences for the individual and for the environment (Dyall 2010).…”
Section: Identification Of Risk and Protective Factorsmentioning
confidence: 99%